Transfer of Secondary Education Management Functions in Central Java Province - Rossy Lambelanova (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2019)
The purpose of this study was to study and analyze the implementation of the transferof management functions for secondary education in Central Java Province, using adescriptive analysis research design with a qualitative approach. The method of datacollection is done by observation, open interviews and analyzing documents. Theanalytical tool in this research is the model of policy implementation proposed by(Smith, 1973), namely there are four important components in the policyimplementation process: (1) ideal policy, (2) implementing organizations (3) targetgroups (4) environmental factors. The results showed that the transfer of themanagement function of secondary education in the Province of Central Java has notrun as expected, this is because the Policy dimension is implemented as aspired(Idealized Policy) has not been fully implemented, especially the Scope sub-dimension,namely aspects funding for the implementation of education is still not fully submittedto the Province, the aspect of asset transfer is still constrained between the district /city government, the Provincial Government and the owner of the foundation, the rangeof control is quite wide because the geographical location of the province of CentralJava is quite extensive with the number of districts / cities that are the largest is 35(thirty-five) districts / cities.